2020
DOI: 10.1126/sciadv.aaz8535
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable structure and tunable transport in synchronized active spinner materials

Abstract: Ensembles of actuated colloids are excellent model systems to explore emergent out-of-equilibrium structures, complex collective dynamics, and design rules for the next generation materials. Here, we demonstrate that ferromagnetic microparticles suspended at an air-water interface and energized by an external rotating magnetic field spontaneously form dynamic ensembles of synchronized spinners in a certain range of the excitation field parameters. Each spinner generates strong hydrodynamic flows, and collectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 49 publications
2
52
0
Order By: Relevance
“…Active spinner fluids, comprised of autonomous spinning units, enable unique dynamic phases and transport characteristics [27][28][29][30][31] . A significant effort, both experimental and theoretical, has been recently dedicated to understanding of fundamental rules governing the emergence of collective states in active colloids comprised of spinning units 28,[32][33][34][35][36][37][38][39] .…”
mentioning
confidence: 99%
“…Active spinner fluids, comprised of autonomous spinning units, enable unique dynamic phases and transport characteristics [27][28][29][30][31] . A significant effort, both experimental and theoretical, has been recently dedicated to understanding of fundamental rules governing the emergence of collective states in active colloids comprised of spinning units 28,[32][33][34][35][36][37][38][39] .…”
mentioning
confidence: 99%
“…2E . In region I, relatively long nanoparticle chains were formed and tended to repel each other because of the strong hydrodynamic repulsion ( 28 , 29 ). By adjusting the field parameters ( d ms and frequency of magnetic field f ), chains were fragmented into shorter chains, and a dynamic-equilibrium microswarm was formed (∼800 μm in radius, region II).…”
Section: Resultsmentioning
confidence: 99%
“…Recently developed approaches exploiting dynamic self‐assembly of magnetic colloidal particles provide a robust method for generating large ensembles of microscopic spinners [46–48] . It has been demonstrated that the application of a uniaxial external magnetic field oscillating in‐plane of the interface supporting ferromagnetic spherical particles can lead to multiple self‐assembled spinners with a narrow size distribution, see Figure 8.…”
Section: Collective Phases In Spinner Materialsmentioning
confidence: 99%
“…Transport characteristics of such spinner liquids are not trivial. The active diffusion (diffusive motion of passive particles promoted by the activity of the spinner sub‐system) increases linearly with the spinner density and is approximately independent of the frequency of the driving field [48] . Moreover, it was demonstrated that the dependence of the active diffusion coefficient on the inert particle size is non‐monotonic.…”
Section: Collective Phases In Spinner Materialsmentioning
confidence: 99%